A novel strategy for hierarchical structure in multicomponent nano-precipitated steels by high magnetic field aging. (15th January 2021) - Qiu, Nianshuang; Yan, Jiacheng; Zuo, Xiaowei
Abstract: The influence of high magnetic field (HMF) during aging on the precipitation behavior of co-precipitates consisted of Cu-rich precipitates and Ni(AlMn) precipitates in multicomponent nano-precipitated steels was carefully investigated. It was indicated that HMF promoted the construction of hierarchical structures of Cu-rich and Ni(AlMn) co-precipitates. It was thought that HMF increased nucleation rates of secondary co-precipitates during aging because of the thermodynamics change, thus refining the secondary precipitates. Meanwhile, HMF increased the Ostwald ripening rate of primary particles during the further aging after tempering because of increasing diffusion of Cu, thus accelerating the coarsening process. Graphical abstract: Image, graphical abstract